Effectiveness of the Red Dragon Fruit (Hylocereus polyrhizus) Peel Extract as the Colorant, Antioxidant, and Antimicrobial on Beef Sausage - Fitri M Manihuruk; Tuti Suryati; Irma Isnafia Arief (Media Peternakan, 2017)
This study aimed to evaluate the effectiveness of red dragon fruit (Hylocereus polyrhizus) peel extracts addition on beef sausages. Red dragon fruit peel extracts were obtained by maceration using solvent at pH 5. Phytochemical characteristics, total phenols, antioxidant, and antimicrobial activity of the peel extracts were observed. Antioxidant and antimicrobial activities of the extracts were associated with high phytochemical compounds and total phenols contained in the extracts. Red dragon fruit peel extracts with various percentages (0%, 20%, 30%, and 40%) were added on beef sausages, and their physicochemical characteristics, nutrients, antioxidant activity, and microbiological profile were analyzed. The data were analyzed using analysis of variance and Duncan’s multiple range test. Results showed that the addition of red dragon fruit peel extracts significantly reduced texture values, but increased intensity of luminosity, intensity of red color, and intensity of yellow color (P<0.05) beef sausages. It could be concluded that red dragon fruit peel extract containing phytochemical compounds was effective as an antibacterial agent and natural antioxidant. The addition of red dragon fruit peel extracts was effective in increasing the antioxidant activity and decreasing TBARS values. The addition of red dragon fruit peel extract did not affect the reddish colorization of beef sausages, but it was capable of increasing the yellowish colorization on beef sausage.